MicroRNA 200b is upregulated in the lungs of fetal rabbits with surgically induced diaphragmatic hernia. (17th July 2018) - Eastwood, Mary Patrice; Deprest, Jan; Russo, Francesca Maria; Wang, Hongmei; Mulhall, Drew; Iwasiow, Barbara; Mahood, Thomas H.; Keijzer, Richard
Abstract: Objective: Profiling of miR‐200b expression and its targets (transforming growth factor [TGF]–β2 and ZEB2) in the surgical rabbit congenital diaphragmatic hernia (DH) model before and after tracheal occlusion (TO). Methods: Thirty‐eight timed‐pregnant rabbits had left DH creation on gestational day (GD) 23. On GD28, 17 randomly selected fetuses had TO. We harvested fetuses at GD23, GD28, or GD30. We calculated lung–to–body weight ratios, processed lungs for miR‐200b in situ hybridization and real‐time quantitative polymerase chain reaction, and evaluated effects on downstream targets TGF‐β2 or ZEB2. Results: We obtained 16 DH fetuses (n = 7 GD28 and n = 9 GD30), 13 TO fetuses (GD30), and 38 control fetuses (n = 15 GD23, n = 11 GD28, and n = 12 GD30). Diaphragmatic hernia lungs were hypoplastic, and TO resulted in control lung–to–body weight ratio levels. Term miR‐200b‐3p levels were significantly upregulated in the hypoplastic compared with control ipsilateral lung (1.906 ± 0.90 vs 0.7429 ± 0.44) ( P < .01). Fetal TO ipsilateral lungs displayed a variable miR‐200b response on in situ hybridization and polymerase chain reaction, with levels similar to control and congenital DH lungs. The TGF‐β2 was unchanged in hypoplastic and TO lungs, and ZEB2 tended to be reduced in TO compared with DH lungs (1.79 [0.4‐2.9] vs 0.73 [0.5‐1.4]). Conclusions: Hypoplastic fetal rabbit lungs display upregulation of miR‐200b expression although downstream targets are not different from controls. Following TO, fetal rabbit lungs display a variable miR‐200b response. Abstract : What's already known about the topic? Human congenital diaphragmatic hernia lungs have upregulated miR‐200b expression. Tracheal occlusion (TO) further upregulates miR‐200b. Responders to TO have higher tracheal fluid miR‐200b levels than nonresponders. What does the study add? Hypoplastic fetal rabbit lungs display upregulation of miR‐200b expression making it a model that can be used for the study of miR‐200b. Following TO, fetal rabbit lungs display a variable miR‐200b response.